2018
DOI: 10.1016/j.chemgeo.2018.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Atom probe tomography analysis of the reference zircon gj-1: An interlaboratory study

Abstract: This is a repository copy of Atom probe tomography analysis of the reference zircon gj-1: An interlaboratory study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Several recent studies have compared APT compositional results from geological samples with those from other geoanalytical techniques (Pérez‐Huerta et al , Daly et al , Exertier et al , Reinhard et al , Saxey et al ). Most comparisons provide excellent agreement, within the uncertainty arising from counting statistics in the atom probe data.…”
Section: Performance and Optimisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have compared APT compositional results from geological samples with those from other geoanalytical techniques (Pérez‐Huerta et al , Daly et al , Exertier et al , Reinhard et al , Saxey et al ). Most comparisons provide excellent agreement, within the uncertainty arising from counting statistics in the atom probe data.…”
Section: Performance and Optimisationsmentioning
confidence: 99%
“…These above studies illustrated how APT could be applied to specific research problems. However, there is also an underlying need to better understand the systematics of atom probe data acquisition, ranging and reconstruction variables in geological materials and this has led to a number of papers dealing with APT optimisation in accessory phase analysis (La Fontaine et al , Blum et al , Exertier et al , Reinhard et al , Saxey et al , Verberne et al ).…”
Section: Geoscience Applicationsmentioning
confidence: 99%
“…To investigate the APT performance with regard to quantification, the first important aspect is to appropriately identify the peaks in the mass spectrum [32,33]. Figure 2 shows three typical mass spectra, each containing 0.5-1×10 6 identified ions, with (a) HV pulsing and (b) laser pulsing at 10 pJ and (c) 70 pJ, respectively, obtained from the same APT specimen.…”
Section: Mass Spectramentioning
confidence: 99%
“…Being able to quantify the background level consistently is important as it has been demonstrated that these user‐dependent choices can affect the results within the same data set (Exertier et al . 2018). Instead, the background was estimated by a linear approximation of the background by defining a straight line using the background level before the 207 Pb 2+ peak from a range of 103.24 to 103.34 Da and after the 207 Pb 2+ peak from 103.775 to 103.875 Da range.…”
Section: Discussionmentioning
confidence: 99%